Penyelesaian Kasus Wanprestasi Wawa Rental dalam Sewa Menyewa Mobil - Ramadani, Fathan; Alfahyan, Muhammad Raihan; Fajar, Muhammad Rizky; Haki, Ardiona Raajwa; Ramadhani, Dwi Aryanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
An agreement or other legal event that results in an obligation gives rise to this legal relationship. In the practice of treaty law, problems often arise relating to the debtor's failure to fulfill his obligations to the creditor or his failure to keep his promise. Default, which comes from the Dutch meaning “bad performance”, occurs when a debtor fails to fulfill a promise, whereas performance occurs when a debtor fulfills a contract under civil law. Default means not fulfilling obligations that have been agreed upon in an engagement. Research on default and its settlement in a car rental agreement at Wawa Rental, Sragen Regency, aims to identify various forms of default and how to resolve them in the practice of car rental agreements at Wawa Rental. The results show that there are several forms of default, namely not performing obligations at all, not being able to carry out obligations as promised, being late in carrying out obligations, and taking actions prohibited in the agreement. The settlement of defaults is carried out through deliberation, while court settlement has never been chosen. The default cases discussed in this paper are examples of many similar cases that have occurred in Indonesia. This shows that there are still many Indonesians who ignore the provisions in the agreement that has been agreed upon by both parties.